FORMULASI KERANGKA KONSEPTUAL AKUNTANSI KEUANGAN: SEBUAH DESKRIPSI - Saputra, Praja Hadi (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to describe in the form of a simple overview the structure of financial accounting meta-theory used by accounting standards in the world. A brief comparison made in this study provides an overview of how the two major accounting institutions in the world (FASB and IASB) formulated a conceptual framework and presented fundamental differences from each conceptual framework. In addition, this study also identifies how IFRS becomes a bridge for the difference between the two and creates uniformity in financial accounting standards or what we call harmonization.